Flexure Analysis of Functionally Graded Plates Using {2,2}-Refined Zigzag Theory - Mehmet Dorduncu (Havacılık ve Uzay Teknolojileri Dergisi, 2019)
This study investigates the flexure analysis of functionally graded (FG) plates using {2,2}-refined zigzag plate theory which considers transverse normal deformation along the thickness of plates. The element is free of geometric locking and does not require shear correction factors. The FG plate is composed of silicon carbide (SiC) and aluminum (Al) varying through the thickness of the plate. The volume fractions of the material constituents in the FG plate were functionally tailored according to a power-law. The effective material properties of the plate were evaluated by using the Mori-Tanaka homogenization scheme. The accuracy of the present approach was demonstrated by considering a simply supported FG plate under distributed sinusoidal load. The influence of the compositional gradient exponent on the stress and displacement distributions of the FG plate was investigated. It was observed that the compositional gradient component played a major role on the stress and displacement levels whereas the influence of the compositional gradient exponent was minor on the stress and displacement profiles.